Efektivitas Pelaksanaan Program Bantuan Sosial Tunai (BST) pada Masyarakat yang Terdampak Pandemi Covid-19: Studi Kasus di Kelurahan Tanjungrejo Kecamatan Sukun Kota Malang - Fitri Ariska; Untari, Sri (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2023)
The existence of a cash social assistance program (BST) to deal with the impact of the Covid-19 pandemic in the Tanjungrejo Village, Malang City, in its implementation is inseparable from various problems. The purpose of this study is to describe and analyze the suitability of beneficiaries or KPM (beneficiary families) with the requirements of beneficiaries of the assistance program, describe the flow of implementation of the distribution of the cash social assistance program (BST) and explain the impact of BST on people affected by the Covid-19 pandemic. Researchers used a qualitative approach to the type of case study research. Sources of data obtained through observation, then interviews and documentation. Data analysis was performed by domain analysis through pattern matching. The results showed that the beneficiary families (KPM) in the Tanjungrejo Sub-District were in accordance with the requirements for receiving the cash social assistance program (BST), for the distribution channel that was carried out, namely data verification, card distribution and fund disbursement, then the assistance had an impact on the community, namely the psychological impact, economic impact, social impact and institutional impact.